Decision Support System Scholarship Selection Using Simple Additive Weighting (SAW) Method - Arifitama, Budi (JISA(Jurnal Informatika dan Sains), 2022)
Scholarships are given to students to motivate students and compete with each other in pursuit of the best grades and achievements during their studies. As the name implies, factors such as GPA, competition participation, lecturer recommendations, and organizational participation are the criteria that will be considered for the selection process. In addition, parental income will also be an additional criterion. To minimize errors and reduce bias in the selection process, students who are eligible for scholarships will be assisted by using a Decision Support System (DSS). DSS will support decision making in selecting outstanding scholarship recipients from a pool of alternatives, namely students who register for the outstanding scholarship program by calculating student eligibility based on consideration of the criteria that students have in accordance with predetermined criteria. This calculation is carried out using the Simple Additive Weighting (SAW) method which is suitable for use in Multiple Attribute Decision Making (MADM) problems. As a result, each student will get an eligibility score which will influence the final decision. After the ranking of students who are most entitled to a scholarship according to the system calculations are obtained, the final decision will still be taken by the university.